Analysis of the potential of acid mine drainage generation from the neutralized coal mining tailings - Mihloti Nwamahoza Mdumela; Fhatuwani Sengani (Brawijaya University, 2021)
Mining activities specifically Coal Mining have been long testified to be one of the major contributing factors to environmental crisis, with Acid Mine Drainage (AMD) as one of the leading indicators. The purpose of this study was to assess the potential of AMD generation from neutralized coal mining tailings. In order to achieve the ultimate objective of the study, analysis of chemical composition and mineral content of the tailings using XRF (X-Ray Fluorescence) and XRD (X-Ray Diffraction) respectively, lastly, a static analysis such as ABA (Acid Base Accounting) and TCLP (Toxic Characteristic Leaching Procedure) were also conducted. The results have shown that the studied tailing samples had relatively higher Acid Potential (19 kg CaCO3/t to 20 kg CaCO3/t) versus the Neutralizing Potential (NP) (14 kg CaCO3/t to 18 kg CaCO3/t). It was also found that the Net Neutralizing Potential Ratio (NNPR) is less than zero (-1.5 kg CaCO3/t to -5.40 kg CaCO3/t which indicates that the tailings have the potential to generate acid. The low concentration of CaO indicates acidic potential of the samples because CaO is a buffering mineral. Based on the results of the study, it was concluded that Mine Tailings has the potential to generate acid; therefore, the contamination to the nearby watercourses is extremely possible if necessary remedial actions should be considered.